Review of New Directions for Evaluation, Volume 106: Theorists' Models in Action - Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2006)
The summer 2005 issue of New Directions for Evaluation, "Theorists' Models in Action", edited by Marvin C. Alkin and Christina A. Christie is, in part, inspired by the "Radnor Middle School" case study conducted in the early 1980s (Brandt, 1981). In the Radnor case study notable theorists including Scriven, Stake, Eisner, and Popham were asked to explain how they would evaluate Radnor's humanities curriculum. In this issue Alkin and Christie asked four contemporary theorists-Jennifer C. Greene, Gary T. Henry, Stewart I. Donaldson, and Jean A. King-to describe how they would evaluate the case of the "Bunche-Da Vinci Learning Partnership Academy." The Bunche-Da Vinci Learning Partnership Academy is essentially a "unique partnership between the [school] district and a nonprofit educational company specializing in innovative school interventions for low-performing students" (Eisenberg, Winters, & Alkin, 2005, p. 5).